Pengaruh Kunjungan Wisata, UMKM, Pajak Hiburan, Retribusi Pariwisata Terhadap PAD Kota Surakarta - Prisma Dwi Anggraeni; Nuwun Priyono (Universitas Kristen Maranatha, 2022)
This study aims to analyze the effect of tourist visits on Regional Original Income, Analyze UMKM on Regional Original Incomes, analyze entertainment tax on Regional Original Income, analyze tourism levies on Regional Original Income. In this study using a quantitative descriptive approach. The population of this research is tourist visits, UMKM, entertainment taxes, tourism levies and local revenue (PAD) in the city of Surakarta. The sample in this study has a period of 15 years 2005-2020. The analytical method used in this research is multiple linear regression analysis techniques. The results of this study show that partially tourist visits, UMKM, and entertainment taxes do not have a significant effect on PAD, while tourism levies partially show a significant effect on PAD. The tourist visit, UMKM, entertainment taxes, and tourism levies simultaneously affect PAD. The results of the coefficient of determination of the independent variable PAD are influenced by the dependent variable of tourist visits, UMKM, entertainment taxes and tourism levies of 95.5%, while 4.5% is influenced by other variables.Keywords: Tourist Visits, UMKM, Entertainment Taxes, Tourism Levies, and PAD